Intestinal microbiota metabolism of l-carnitine, a nutrient in red meat, promotes atherosclerosis - Koeth, Robert A; Wang, Zeneng; Levison, Bruce S; Buffa, Jennifer A; Org, Elin; Sheehy, Brendan T; Britt, Earl B; Fu, Xiaoming; Wu, Yuping; Li, Lin; Smith, Jonathan D; DiDonato, Joseph A; et al. (Nature medicine, 2013)
The long-noted association of red meat with an increased risk of cardiovascular disease may be due to ingestion of a specific compound found in red meat, l -carnitine. The ability of this compound to promote atherosclerosis in mice requires that it be further metabolized by the gut microbiota. In humans, omnivores but not vegans or vegetarians metabolize l -carnitine in this manner, a difference which may be explained by effects of diet on the presence of specific types of bacteria in the gut. Intestinal microbiota metabolism of choline and phosphatidylcholine produces trimethylamine (TMA), which is further metabolized to a proatherogenic species, trimethylamine- N -oxide (TMAO). We demonstrate here that metabolism by intestinal microbiota of dietary l -carnitine, a trimethylamine abundant in red meat, also produces TMAO and accelerates atherosclerosis in mice. Omnivorous human subjects produced more TMAO than did vegans or vegetarians following ingestion of l -carnitine through a microbiota-dependent mechanism. The presence of specific bacterial taxa in human feces was associated with both plasma TMAO concentration and dietary status. Plasma l -carnitine levels in subjects undergoing cardiac evaluation ( n = 2,595) predicted increased risks for both prevalent cardiovascular disease (CVD) and incident major adverse cardiac events (myocardial infarction, stroke or death), but only among subjects with concurrently high TMAO levels. Chronic dietary l -carnitine supplementation in mice altered cecal microbial composition, markedly enhanced synthesis of TMA and TMAO, and increased atherosclerosis, but this did not occur if intestinal microbiota was concurrently suppressed. In mice with an intact intestinal microbiota, dietary supplementation with TMAO or either carnitine or choline reduced in vivo reverse cholesterol transport. Intestinal microbiota may thus contribute to the well-established link between high levels of red meat consumption and CVD risk.